Design of a multiple-model switching controller for ABS braking dynamics. (May 2015) - Dousti, Morteza; Baslamısli, S Caglar; Onder, E Teoman; Solmaz, Selim
The purpose of this study is to design high-performance active braking control and observer algorithms for passenger vehicles equipped with electromechanical brake systems. These algorithms are designed to be adaptive with changing driving and road conditions in a switched multiple-model manner to ensure high performance and robustness. The effectiveness of a set of multiple-model switching lead-lag controllers is evaluated during transitions between different road friction coefficients. Meanwhile, a multiple-model switching observer algorithm is developed to estimate the shape of the tyre braking force curve with respect to the longitudinal slip. Each switched observer predicts signals according to its preset tyre model. The observers are designed based on different Burckhardt tyre models that are parameterized for different road conditions. In our simulations, the value of the friction coefficient is assumed to be unknown and our switching algorithms are observed to estimate successfully the varying friction coefficients by comparing a quadratic cost function of measured signals from the vehicle with signals generated by observers. We demonstrate that our algorithms provide high reliability and fast response, thus ensuring a stopping distance close to the theoretical minimum.